Effects of ground bamboo application on weed suppression and rice production: a 3-year paddy field experiment - Masfiro Lailati; Yichen Shang; Thien Quang Huynh; Koji Ito; Naoya Katsumi; Yumiko Mizuuchi; Masaya Ino; Tadao Takashima; Nisikawa Usio (CABI Agriculture and Bioscience)
Abstract Background In light of the dramatic expansion of Japan’s bamboo forests, it is necessary to develop a strategy for the effective use of bamboo biomass resources. In this study, we tested the effects of ground bamboo as an organic mulching material or soil conditioner during a 3-year, agrochemical-free rice cultivation period. Methods We performed field experiments in 16 experimental paddy fields and established five treatments with three or four replicates each: control, manual weeding, low-volume ground bamboo application (0.5 kg m−2), medium-volume ground bamboo application (1.0 kg m−2), and high-volume ground bamboo application (2.0 kg m−2). Results We observed no suppression of aquatic weeds with the ground bamboo treatments. Nevertheless, in the first year, rice yields were 1.7–1.8 times greater in the medium- and high-volume ground bamboo treatments than in the controls. In the second and third years, rice yields did not differ among treatments. During the 3-year period, mean rice yields dropped dramatically to around 20%. Simple linear regression analyses indicated that rice yields were positively associated with available phosphate, and negatively associated with the silicic acid content of post-experiment paddy soils after the second and third years of cultivation. Multiple linear regression analyses indicated that available phosphate and silicic acid were important variables explaining rice yields. Application of ground bamboo did not appear to reduce external rice grain quality. Conclusions Application of ground bamboo may enhance the production of high-quality rice, particularly when soil phosphorus is not deficient.